Phosphorylated chitosan and nano-sized TMP: Enhancing strength, antibiofilm action, and biocompatibility of restorative glass ionomer cements: Effect of incorporating chitosan and NP phosphate into a restorative cement formulation - Piati, Gabrielle Cristina; Silva, Danielly Beatriz Gonçalves; Delbem, Alberto Carlos Botazzo [UNESP]; Martorano, Antônio Secco; Raucci, Larissa Moreira Spinola de Castro; de Oliveira, Paulo Tambasco; Zucolotto, Valtencir; Dias, Bruna Juliana Moreira; Brighenti, Fernanda Lourenção [UNESP]; de Oliveira, Analú Barros [UNESP]; Moraes, João Carlos Silos [UNESP]; de Camargo, Emerson Rodrigues; et al. (Elsevier, 2025)
Objectives: Evaluated the effect of phosphorylated chitosan (ChiPh) and nano-sized sodium trimetaphosphate (TMPnano) incorporation into resin modified glass ionomer cement (RMGIC) on mechanical, fluoride release, antimicrobial and cytotoxic properties. Methods: RMGIC was combined with ChiPh (0.25 %/0.5 %) and/or TMPnano (14 %). The diametral compressive/tensile strength (DCS/TS), surface hardness (SH) and degree of conversion (%DC) were determined. For fluoride (F) release, samples were immersed in DE/RE solutions. Antimicrobial/antibiofilm activity was evaluated by agar diffusion test/biofilm metabolism. Cytotoxicity on MDPC-23 odontoblast cell lines was evaluated. Results: TS and DCS (24 h), all the groups were similar (p > 0.05). After 7 days, RMGIC-14 %TMPnano-0.25 %ChiPh showed the best results for TS/DCS (p < 0.05). The SH was lower and similar for the RMGIC and RMGI-14 %TMPnano-0.5 %ChiPh groups (p > 0.05) after 24 h; after 7 days, all groups containing TMPnano and/or ChiPh showed higher SH when compared to RMGIC, except for RMGIC-0.5 % ChiPh. The %DC was similar for all groups (p = 0.172). There was a gradual release of F for all groups during the 15 days; in the cumulative analysis, after 15 days, the RMGIC-14 %TMPnano-0.25 %ChiPh group showed the highest value (p < 0.05). Viability against S. mutans was observed for the RMGIC-14 %TMPnano-0.25 %ChiPh group (p < 0.05). After 24 h, the RMGIC-0.25 %ChiPh and RMGIC-14 %TMPnano-0.25 %ChiPh groups showed the lowest cytotoxic effect (p = 0.371); at 48 h/72 h, only the RMGIC-14 %TMPnano-0.25 %ChiPh group showed similar cytocompatibility. Conclusion: The addition of ChiPh (0.25 %) and TMPnano (14 %) improved the RMGIC's mechanical, antimicrobial/antibiofilm and cytotoxic properties. Clinical relevance: ChiPh and TMPnano into RMGIC could be a promising restorative material for application in patients with active dental caries.
Keywords: Biofilm; Chitosan; Cytotoxicity; Glass ionomer cement; Mechanical tests; Nano-sized; Phosphates